Clays and Clay Minerals, Vol. 57, No. 1, 136, 2009. - Quirk, James P. (My University, 2009)
The Marilyn and Sturges W. Bailey Distinguished Member Award of The Clay Minerals Society was made to Dr Keith Norrish, CSIRO Division of Soils, Adelaide, Australia, at the 38th annual meeting of The Clay Minerals Society in Madison, Wisconsin, on June 18, 2001. The following introduction was made on behalf of the recipient.
Marilyn And Sturges W. Bailey Distinguished Member Award 2001
gsccm57113-qui.pdf : 127KB
Keywords: Periodicals; Geology; Marilyn and Sturges W. Bailey Distinguished Member Award of The Clay Minerals Society